Musik und Melancholie im Werk Heimito von Doderers - Brinkmann, Martin (2012)
The present book consists of two parts, thus embodying the "two forces" that Bakhtin sees at play in every work of art: form and content. They are accorded equal weight. With regard to form, the book explores the various literary strategies employed by Doderer in his "Divertimenti," in as much as they are inspired by musical forms. With regard to content the book focuses on the rather gloomy subjects that dominate the "Divertimenti." The aim is to explore in how far these two aspects, i.e. musical form - a superstructure informed by musical aesthetics - and melancholic content - an oppressive atmosphere, the explicit foregrounding of experiences of depression - depend on each other. The book shows how they form a compelling whole. It is based on a variety of unpublished primary sources that have not been studied before, including an early fragment of "Divertimento No VI" ("Erwachen fröhlicher Empfindungen bei der Ankunft auf dem Lande") as well as diary sketches and draft outlines of the composition of the work. The book is thus able to comprehensively explore the musical techniques and strategies of musical composition of the "Divertimenti." This thorough formal analysis provides new insights into what Steven Paul Scher has called an area of "comparative liminality" - that area in which the conditions are negotiated under which musical techniques can be transferred into "literature." The "Divertimenti" belong to the world of Saturn. By focusing on melancholy and depression - topics that resonate throughout the Divertimenti and provide the dark undertone of the author's later works - the book offers a new reading of Doderer's work; it brings to light depictions of "deperceptive" states. This requires a new explanation of Doderer's own theory of "apperception" and "deperception," and of "first" and "second reality." It will be offered in light of Kristeva's "dark sun." The book explores depictions of melancholy in a broader context and considers potential links between literary and clinical manifestations of melancholy. In view of the intellectual milieu of contemporary Vienna, the present study shows how deeply indebted Doderer's early works are to Viennese Modernism - a quality that has been obstructed by the fact that most of these works were only published after Doderer's death. This presupposes an appreciation of the Wiener Moderne which goes beyond the time span suggested by Gotthart Wunberg's 1981 anthology, "Die Wiener Moderne. Literatur, Kunst und Musik zwischen 1890 und 1910," instead drawing inspiration from "Wien 1880-1938. Die fröhliche Apokalypse," a 1986 exhibition at the Centre Pompidou in Paris which, according to Jacques Le Rider, epitomizes the study of Viennese Modernism. Doderer's receptivity for the intellectual, theoretical, and artistic movements of the turn of the 20th century is shown to be more pronounced than previously assumed. While the ambition of Doderer's works ultimately transcends Viennese Modernism, a close exploration of the central tenets of this period can highlight various aspects of his early works, especially his uncompromising will to (musical) form.